THE ENVIRONMENTAL IMPACTS OF THE œMARITIME AUTONOMOUS SURFACE SHIPS (MASS) - Zanella, Tiago Vinicius (Veredas do Direito, 2021)
Autonomous ships are already a reality. They are on the agenda of international law and international society in general. In a short time, it will also be a reality in all the world™s oceans. Thus, international organizations, States and international society need to be prepared for these autonomous ships. They will bring new challenges to the law of the sea and international maritime transport. One of these challenges is just what are the environmental impacts that these œMaritime Autonomous Surface Ships (MASS) will bring with them. That is, what are the consequences for the marine environment of these autonomous ships? This is precisely the objective of this article: to understand the environmental impacts of MASS and what are the new challenges that humanity will have to face the imminent advent of these ships. In this sense, it will be demonstrated what the advantages and disadvantages of these vessels for the environment are and, in particular, what care the world needs to take to protect and preserve the marine environment due to the advent of these new technologies.